Enhanced biogas biological upgrading from kitchen wastewater by in-situ hydrogen supply through nano zero-valent iron corrosion. (15th May 2022) - Tang, Jieyu; Liu, Ziyi; Zhao, Mingxing; Miao, Hengfeng; Shi, Wansheng; Huang, Zhenxing; Xie, Lijuan; Ruan, Wenquan
Abstract: The in-situ hydrogen supply by nano zero-valent iron (nZVI, nFe 0 ) corrosion provided a feasible way to improve the efficiency of biogas biological upgrading. This work studied the effects of nZVI at different dosages (0, 2, 4, 6, 8 and 10 g/L) on anaerobic digestion of kitchen wastewater by two buffer systems 2-[4-(2-hydroxyethyl) piperazin-1-yl] ethanesulfonic acid (HEPES) and sodium hydrogen carbonate (NaHCO3 ). The addition of nZVI improved the content of methane (CH4 ) and stability of anaerobic digestion process. In HEPES buffer system, the CH4 was all increased and the maximum reached 90.51% with 10 g/L nZVI, higher than 32.25% compared to the control. The maximum hydrogen enrichment (HE) was 113 ppb after nZVI addition, indicating the mass transfer efficiency of hydrogen (H2 ) was improved. Microbial community analysis showed that the total relative abundance of Methanobacterium and Methanolinea at 10 g/L nZVI was 53.72%, which was 1.62 times of the control group. However, in the NaHCO3 buffer system with 10 g/L nZVI addition, the content of CH4 and the loosely bound extracellular polymeric substances (LB-EPS) was lower than the control. The results indicated that the addition of nZVI was feasible for biogas upgrading, and the bidirectional effect of nZVI on the promotion or inhibition of bio-methanation might be related to the buffer system of the anaerobic process. Graphical abstract: Image 1 Highlights: In-situ hydrogen evolution by nano zero-valent iron could enhance methane content. Different buffer systems could affect the performance of biogas upgrading. 10 g/L nano zero-valent iron led to the highest methane content of 90.51% (v/v). Changes of microbial community after adding nano zero-valent iron was explored.